Wild horses - Byler, Linda (Intercourse, PA : Good Books, 2011)
The Miller family's move from Ohio to Montana was uneventful. But now, Sadie's close-knit family is falling apart. And who is this fascinating Mark who helps to rescue a dying horse and shows up at the Amish hymn sing though he is English? And what is the story behind the mysterious wild horse?
Keywords: Amish -- Fiction; Horses -- Fiction; Montana -- Fiction; Love stories; Christian fiction; Love stories; Christian fiction